Pengaruh Viral Marketing Terhadap Keputusan Pembelian Poco Smartphone: Survei Pada Grup Facebook Poco X3|X3 PRO|X3 GT Indonesia - Ammar Fakhrudin; Oktaviana Purnamasari (Lembaga Pengembangan Kinerja Dosen, 2024)
Viral Marketing is the digital version of Word of Mouth marketing, involving the creation of videos, advertisements and other marketing content that is so contagious that customers will search for it or share it with friends. Poco Smartphone is a product that implements viral marketing activities by launching a product that is different from the others. The purpose of this research is to determine viral marketing, purchasing decisions, and the magnitude of the influence of viral marketing on Poco Smartphone purchasing decisions. The theories used in this research are marketing communication theory, viral marketing theory, social media theory, and Purchasing Decision theory. This research is quantitative research with a survey method and the data collection technique used was using a questionnaire. The population in this study was 2464 members of the Poco X3|X3 PRO|X3 GT Indonesia Facebook group and the sample used was 96 respondents who were calculated using the Taro Yamane formula. The sample data collection technique in this study used simple random sampling. This research uses simple linear regression data analysis techniques. The results of this research show that there is an influence between 1) viral marketing providing good results from statements in each dimension of messengers, messages and environment with an average gain of 4.19. 2) purchasing decisions provide good results from statements for each dimension such as Problem Recognition, Information Search, Alternative Evaluation, Purchase Decision, and Post-Purchase Behavior with an average of 4.26. 3) The influence of viral marketing on Poco smartphone purchasing decisions has a high level of influence, as can be seen from the large correlation value (r) of 0.866 and the R Square value of 0.749, which means that variable X (Viral Marketing) is influenced by variable Y (Purchasing Decision) of 74 .9%, while the remaining 25.1% is influenced by other factors outside of this research.